Analysis of the Influence of Capital Structure, Ownership Structure, and Good Corporate Governance on Financial Performance at CV. Lestari Jaya Purnama - Jesita Almanna; Etty Harya Ningsi; Selvi Aristantya (Brilliant International Journal Of Management And Tourism, 2026)
This study aims to examine the effect of capital structure, ownership structure, and good corporate governance (GCG) on the financial performance of CV. Lestari Jaya Purnama. Financial performance is a crucial indicator of a company’s sustainability and reflects the effectiveness of managerial decision-making. This research employs a quantitative approach with an associative design to analyze the relationships among variables. Primary data were collected through structured questionnaires distributed to employees who are directly involved in financial and managerial activities within the company. The data were analyzed using multiple linear regression to determine both partial and simultaneous effects of the independent variables on financial performance.The findings reveal that capital structure has a positive and significant effect on financial performance, indicating that an optimal proportion of debt and equity can enhance company profitability and efficiency. Ownership structure shows a negative effect on financial performance, suggesting that certain ownership compositions may reduce managerial flexibility and decision-making effectiveness. Meanwhile, good corporate governance has a positive and significant effect on financial performance, demonstrating that transparency, accountability, responsibility, independence, and fairness contribute to better financial outcomes. Furthermore, the simultaneous test results indicate that capital structure, ownership structure, and GCG collectively have a positive and significant influence on financial performance. These findings imply that strengthening governance practices and optimizing capital decisions are essential strategies for improving the financial performance of CV. Lestari Jaya Purnama.